Tinea Corporis - Nurhaliza Nurhaliza; M. Mimbar Topik (Nian Tana Sikka : Jurnal ilmiah Mahasiswa, 2024)
The patient is 13 year old female, came with her family to the Cut Meutia Hospital Polyclinic with complaints of a red rash spreading across the back of her thighs, stomach and face which had been accompanied by itching for the past 3 months. Complaints of itching come and go and get worse when she was sweat more after activity. The patient also complained that the itching made her sleepless. This primary data was obtained through autoanamnesa, alloanamnesa and physical examination at Cut Meutia Hospital. The assessment is carried out based on the initial holistic diagnosis, process and end of the visit to the clinic with by quantitatively and qualitatively. The interventions carried out include education regarding the causes and prevention that can be done for tinea corporis as well as personal hygiene that can be carried out in order to prevent the emergence of tinea corporis and break the chain of transmission. Apart from that, education regarding management and explaining complications that can occur so that patients want to seek treatment and take preventive measures.